Pemanfaatan Platform E- Commerce Untuk Menaikkan Omset Penjualan UMKM - Puteri Mutiara Dita; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
Utilization of e-commerce platforms has become an important strategy in increasing sales turnover for Micro, Small and Medium Enterprises (MSMEs). Digitalization through e-commerce allows MSMEs to expand market reach, increase operational efficiency, and introduce products to a wider range of consumers without geographic limitations. This research aims to analyze the positive impact of using e-commerce platforms on increasing MSME sales turnover, the factors that influence technology adoption by MSMEs, as well as the challenges faced in the digitalization process. Data was collected through survey methods and literature studies on MSMEs that have implemented e-commerce strategies. However, obstacles such as limited technological knowledge and capital are the main challenges for MSMEs in adapting to e-commerce platforms. Therefore, support is needed from the government and various related parties in providing training, access to capital and adequate digital infrastructure for MSMEs to maximize the potential of e-commerce.